(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
De- and re-hydroxylation of different silica gel samples’ surfaces were studied by IR-spectrometry method. Based on data of differential thermal heat of ethanol and water adsorption it was shown the energetic non-uniformity of samples’ surface regarding to polar molecules. It was proved that the surface of silica gel obtained from serpentinite is energetically more homogeneous.